A PRE EXPERIMENTAL STUDY ON THE EFFECTS OF ANIMATED VIDEOS ON STUDENTS’ LISTENING COMPREHENSION - Maulidina Akmil; Dwi Agustina (PROCEEDING OF NATIONAL SEMINAR ON LITERATURE, LINGUISTICS AND LANGUAGE TEACHING, 2026)
This study aims to examine the effects of animated videos on students’ listening comprehension. A quantitative approach with a pre-experimental design employing a one-group pre-test and post-test was utilized. The participants consisted of 33 tenth-grade students. Data were collected through listening comprehension tests administered before and after the treatment. The treatment involved the integration of animated videos into listening activities. The findings revealed a statistically significant improvement in students’ listening comprehension, as indicated by an increase in the mean score from 40.91 in the pre-test to 65.61 in the post-test (p = <0.001). This result indicates that animated videos provide effective visual and auditory input that supports students’ comprehension processes. In conclusion, animated videos serve as an effective instructional medium for enhancing students’ listening comprehension. Accordingly, animated videos may serve as an effective medium to enhance students’ listening comprehension.